2021
DOI: 10.1002/jcc.26520
|View full text |Cite
|
Sign up to set email alerts
|

Non long‐range corrected density functionals incorrectly describe the intensity of the CH stretching band in polycyclic aromatic hydrocarbons

Abstract: We present a comprehensive study of the most relevant numerical aspects influencing frequencies and intensities in the infrared spectrum of isolated polycyclic aromatic hydrocarbons (PAHs) regarding the overestimate of the IR CH-stretching bands. We use naphthalene as benchmark and show the validity of our results to different members of the PAH family. Our analysis relies on widely employed density functional theory methods and second-order vibrational perturbational theory for the computation of vibrational … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…However, considering the intensities, the harmonic, relatively low-level calculations are known to consistently overestimate the CH stretch band intensity. 29 To corroborate these ndings, in Fig. 2 we compare the calculated ratio from the PAHdb with the ratio determined from gas-phase direct absorption measurements from the NIST database.…”
Section: Theory and Gas-phase Experimentsmentioning
confidence: 78%
See 1 more Smart Citation
“…However, considering the intensities, the harmonic, relatively low-level calculations are known to consistently overestimate the CH stretch band intensity. 29 To corroborate these ndings, in Fig. 2 we compare the calculated ratio from the PAHdb with the ratio determined from gas-phase direct absorption measurements from the NIST database.…”
Section: Theory and Gas-phase Experimentsmentioning
confidence: 78%
“…Even more so because it was noticed already in the 90s by Langhoff and later by others that the intensity ratios derived at different levels of theory can vary signicantly. [27][28][29][30] First, the use of a small basis set results in an overprediction of CH stretch intensities by about 20% when compared to matrix-isolation absorption spectra. 27 Secondly, it was recently shown that anharmonicity leading to phenomena such as combination bands and resonances has a dominant effect on the CH stretch region of the IR spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, as it will be shown, the conformational changes in the reaction network are associated with weak changes in the (non‐covalent) interactions, thus implying variations of the energy of the order of tenths of wavenumbers. These slight variations, such as those involved in small‐step optimizations, are close to the numerical accuracy of the employed algorithms [26,27] . Consequently, minimizing the human‐in‐the‐loop is (almost) a necessity and automated calculations become mandatory.…”
Section: Introductionmentioning
confidence: 79%
“…[26] As for the high level, all stationary points geometries, minima, transition states, and IRC final step geometries have been optimized at the UωB97XD/cc-pVDZ level of theory, using the tight convergence criterion and a SuperFineGrid for the DFT integrals. [27,52] Notably, we use the unrestricted formalism due to the radical character of NO 2 in its ground electronic state. The proposed level of theory has been shown to be suitable for similar systems where accurate descriptions of long-range dispersion forces and exchange-correlation effects are required.…”
Section: Vdw-tsscds: Low-and High-levels Of Electronic Structure Theorymentioning
confidence: 99%
See 1 more Smart Citation